PENGARUH DIGITAL MARKETING, BRAND AWARENESS DAN BRAND IMAGE TERHADAP MINAT BELI PADA PRODUK SOMETHINC DI KOTA BATAM - Aurellia Calista; Evyanto, Winda (LPPM Universitas Putera Batam, 2025)
The rapid development of digital technology in the 21st century has significantly transformed marketing strategies from traditional methods to predominantly digital approaches, with internet penetration in Indonesia reaching 79.5% in 2024 and social media becoming the primary information source for consumers. This study aims to analyze the influence of digital marketing, brand awareness, and brand image on purchase intention of Somethinc products in Batam City. Somethinc, a local skincare brand launched in 2019, initially achieved remarkable success through TikTok digital marketing strategies, reaching the top position as the most popular skincare brand with 57.3 million hashtag views in 2020 and generating sales of Rp 53.2 billion during April-June 2022. However, the brand experienced significant performance decline, dropping from first position in 2022 to ninth position in March-April 2024, and even failing to appear in the